An Analytical Study of Relationship of Kamma and Saṃsāra in Theravāda Buddhism - Kruadsungnoen, Phra Sornnaret Issariyo; Thangthongmadan, Sathien; Rakkhitadhammo, Phamaha Suporn (Journal of Dhamma for Life, 2026)
This research article aims to: (1) examine the concept of kamma (karma) in Theravāda Buddhism, (2) investigate the concept of saṃsāra (the cycle of rebirth) in Theravāda Buddhism, and (3) analyze the relationship between kamma and saṃsāra according to Theravāda Buddhist teachings. The study employs qualitative documentary research, drawing data primarily from the Pāli Canon (Tipiṭaka), its commentaries, and related scholarly works. The data were collected through document analysis and systematically analyzed using content analysis, with findings presented in a descriptive and analytical manner. The population and sample of the study consist of primary and secondary Buddhist texts relevant to the doctrines of kamma and saṃsāra. The research instruments include document recording forms, while data analysis focuses on categorizing doctrinal concepts and interpreting them based on Buddhist principles. The findings reveal that kamma in Theravāda Buddhism does not merely refer to action in a general sense, but specifically to intentional actions of body, speech, and mind, with volition (cetanā) serving as the determining factor. Such intentional actions function as a significant causal force that conditions rebirth and perpetuates existence within saṃsāra. Kamma is classified into various types according to the nature and result of its fruition, thereby sustaining beings within the cycle of suffering. Furthermore, the concept of saṃsāra is clearly explained as the continuous process of arising and ceasing of the five aggregates, governed by causal conditions. When kamma functions as a cause, rebirth arises as its result, and rebirth in turn provides the basis for the generation of new kamma. This cycle persists as long as ignorance (avijjā) and craving (taṇhā) remain operative. The analysis demonstrates that kamma and saṃsāra are intrinsically interconnected, with kamma serving as both the cause and driving force of cyclic existence. Understanding this relationship is therefore fundamental to the cultivation of wisdom and the pursuit of liberation from the cycle of suffering in accordance with Theravāda Buddhism.